Evaluation of clinical knowledge and perceptions about the development of thyroid cancer—An observational study of healthcare undergraduates in Saudi Arabia - Syed, Wajid; Samarkandi, Osama A.; Alsadoun, Ahmed; Harbi, Mohammad K. Al; Al-Rawi, Mahmood Basil A. (Frontiers in Public Health, 2022)
Background and objective In the healthcare context, healthcare personnel are available to help patients according to their requirements. However, having sufficient knowledge of many elements of diseases before graduation may have a good impact on clinical practices later in one's career. As a result, the purpose of this study was to assess the clinical knowledge and perceptions of healthcare students in Saudi Arabia about thyroid cancer (TC). Methods A cross-sectional study was conducted in King Saud University from August 2021 to November 2021, using a validated self-reporting online survey. The data collection was carried out among senior healthcare students, including pharmacy, nursing, and medical students of both genders, who were Arabic speakers. The data were analyzed using the Statistical Package for the Social Sciences version 26 for Windows (SPSS). Results There were 141 healthcare students who responded, with 46.8% (n = 66) being pharmacy students, 28.4% (n = 40) being nursing students, and 24.8% (n = 35) being medical students. Male participants made up the majority of them (52.5%). Lump or swelling in the neck was described as the most common early indicator of TC by 54.6% (n = 77), followed by difficulty in swallowing by 34.04% (n = 48), and pain in the neck by 24.8% (n = 35). Female participants accounted for 44.7% (n = 63) of those with thyroid dysfunction, according to the study. About 55.3% of the participants (n = 78), reported that they had sufficient knowledge about TC. The knowledge score differed significantly by gender; female participants (60.3%) (n = 47) were more knowledgeable than male participants (30.7%) (n = 31) (p = 0.049). Conclusion This study depicts that half of the healthcare students thatwere knowledgeable about TC had positive perceptions about the causes of diseases. Furthermore, we also recommend arranging awareness programs for the students by the university officials to overcome the knowledge gap.